Fungsi Badan Usaha Milik Desa (Bum Desa) Maju Sejahtera dalam Meningkatkan Kesejahteraan dan Kemandirian Masyarakat di Desa Ngampungan Kabupaten Jombang - Natasya Firdaus Supriyanto; Oktarizka Reviandani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Poverty is often experienced by rural communities due to a lack of means to fulfill basic needs, as well as difficulties in accessing education and employment. The high level of poverty in rural areas is caused by various factors such as the level of education, low motivation, few jobs, the number of dependents, and differences in access to resources. Therefore, an economic institution that is able to utilize the potential of the village is needed. BUM Desa is present with the aim of improving the village economy through the establishment of business units. The purpose of this study was to determine the role of BUM Desa in improving the economy in Ngampungan Village. The research method used in this research is qualitative research. The results showed that the role of BUM Desa in improving the economy in Ngampungan Village is 1). as a driving force for the village economy, by developing appropriate businesses based on village potential and establishing cooperation with other village institutions. 2) as a business institution that produces PAD, by opening business units that generate profits, developing innovations for BUM Desa businesses 3) as a means to encourage the acceleration of improving the welfare of rural communities, namely by establishing partnerships with village communities and opening up jobs for rural communities.